FADD regulates antibacterial immune responses via the immune deficiency signaling pathway in the Chinese mitten crab. (March 2022) - Zhou, Kaimin; Bai, Longwei; Nan, Xingyu; Zhao, Ke; Song, Yu; Li, Weiwei; Wang, Qun
Abstract: In invertebrates, innate immune responses are the only defense against invading pathogens. The immune deficiency (IMD) signaling pathway protects invertebrates from bacterial infection by secreting antimicrobial peptides (AMPs). Fas-associated protein with death domain (FADD) activates AMPs and triggers apoptosis. However, FADD's function in crustaceans is unclear. Herein, the full-length FADD cDNA ( EsFADD ) was cloned from the Chinese mitten crab, Eriocheir sinensis . Vibrio parahaemolyticus infection upregulated EsFADD expression markedly. Knockdown of EsFADD in hemocytes suppressed the cytoplasm-to-nucleus translocation of transcription factor Relish under V. parahaemolyticus stimulation, which in turn reduced the expression of several AMPs. In vivo, silencing of Es FADD rendered crabs susceptible to bacterial infection and impaired their bacterial clearance. The results suggest that Es FADD is indispensable in IMD signal transduction in E. sinensis . In contrast to Drosophila, Es FADD barely promoted apoptosis. Our findings revealed the evolutionary conservation of FADD in crustaceans and provided insights into IMD signaling in invertebrates. Highlights: The full length of a FADD gene from Eriocheir sinensis ( Es FADD) was cloned and characterized. The expression of Es FADD was significantly upregulated by stimulation with V. parahaemolyticus . Es FADD regulates antibacterial immune responses via IMD signaling pathway in E. sinensis . Es FADD has feeble role in inducing apoptosis.